1997
DOI: 10.1056/nejm199702273360903
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass and the Risk of Breast Cancer among Postmenopausal Women

Abstract: Women in the highest quartile of bone mass are at higher risk for postmenopausal breast cancer than those in the lowest quartile. The mechanisms underlying this relation are not understood, but cumulative exposure to estrogen may play a part.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
111
1
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(125 citation statements)
references
References 58 publications
10
111
1
3
Order By: Relevance
“…In the majority of older adults, bone mineral density (BMD) predictably decreases with age, with osteoporotic fractures as an end product (Cauley et al 2009). Osteoporosis traits have been associated with risk for multiple diseases, including coronary disease in women (Samelson et al 2004), and with risk for breast, colon and prostate cancer (Zhang et al 1997(Zhang et al , 2002, memory impairment (Zhang et al 2001) and dementia in women (Tan et al 2005) and a higher risk of mortality independent of age and comorbidities (Van Der Klift et al 2002;Bauer et al 2002). Most recently, Cauley et al (2009) suggested that maintenance of BMD may represent a clinical phenotype of successful aging.…”
Section: Biomarkers Of Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of older adults, bone mineral density (BMD) predictably decreases with age, with osteoporotic fractures as an end product (Cauley et al 2009). Osteoporosis traits have been associated with risk for multiple diseases, including coronary disease in women (Samelson et al 2004), and with risk for breast, colon and prostate cancer (Zhang et al 1997(Zhang et al , 2002, memory impairment (Zhang et al 2001) and dementia in women (Tan et al 2005) and a higher risk of mortality independent of age and comorbidities (Van Der Klift et al 2002;Bauer et al 2002). Most recently, Cauley et al (2009) suggested that maintenance of BMD may represent a clinical phenotype of successful aging.…”
Section: Biomarkers Of Agingmentioning
confidence: 99%
“…The process of bone and muscle involution is a general phenomenon and a typical manifestation of tissue atrophy with age (Plato et al 1994). Studying the musculoskeletal aging provides a "local" model from which "global" inference for aging can be driven since the musculoskeletal biomarkers are linked to the state of many vital functions, age-related conditions of different bodily systems (Zhang et al 1997;Samelson et al 2004;Browner et al 1993), cardiovascular disease (Hak et al 2000;Kiel et al 2001), cancer, mortality, disability, and ultimately survival rates (Kiel et al 2001;Johansson et al 1998). We therefore postulate that by studying musculoskeletal aging-as a proof of principle-we can come closer to the understanding of an organism's aging.…”
mentioning
confidence: 99%
“…High serum oestrogen levels (Toniolo et al, 1995;Thomas et al, 1997;Hankinson et al, 1998;Cauley et al, 1999;Key et al, 2002;Missmer et al, 2004) and surrogates for long-term high oestrogen exposure, such as bone (Zhang et al, 1997) density, are known to be associated with an increased risk for breast cancer. However, exposure to anti-oestrogens has been shown to decrease the risk for breast cancer and recurrent disease (Baum et al, 2002;Cuzick et al, 2003).…”
mentioning
confidence: 99%
“…Regression analyses of these log-transformed values therefore were used to evaluate their relationship with age and menopausal status and showed that these variables needed to be accounted for when comparing androgen levels with respect to breast cancer risks. To achieve this we classified women according to strata defined by age and menopause categories and, within each stratum, assigned women into A and E tertiles, adapting the method described by Zhang et al (1997) (see Appendix). Stratum-specific rates for breast cancer incidence were then estimated for these age-and menopause-adjusted tertiles of androgen levels and for categories of the potential confounders for which information had been collected: age at menarche (≀ 12, 13, >13), parity (0, 1+), age at first birth (≀ 20, 21-25, > 25, nulliparous), self-reported height and weight (both in tertiles) and body mass index (BMI = (wt (kg))/(ht(m)) 2 ; also in tertiles).…”
Section: Methodsmentioning
confidence: 99%